Social withdrawal subtypes and psychological well-being in Chinese emerging and early adults: unsociability as a protective factor and age-differentiated effects in a new media social environment - Kishimoto, Tomoko; Wang, Tianyu; Bai, Qiyu (Frontiers in Psychiatry, 2025)
IntroductionIn the digital age, social withdrawal as a stable personality trait has become increasingly complex, as individuals may engage in face-to-face withdrawal while maintaining digital social connections through new media platforms. Well-established withdrawal subtypes have been studied in Western cultures, but their implications in Chinese digital social contexts remain underexplored.MethodsThis cross-sectional study examined the associations between different social withdrawal subtypes and psychological well-being indices among Chinese emerging and early adults, with consideration of the contemporary digital social landscape. Participants (n = 1365, M_age = 27.79) completed an online survey including the Social Preference Scale for Adult-Chinese Revised (SPSA-CR), measures of psychological well-being, and relationship satisfaction.ResultsResults showed that each social withdrawal subtype was differentially associated with psychological well-being indices: shyness was significantly associated with internalizing problems, externalizing problems, and relationship satisfaction; avoidance was significantly associated with internalizing problems and relationship satisfaction; unsociability was significantly associated with aggression and relationship satisfaction. Age moderated the associations between shyness and psychological well-being indices, though effect sizes were small (β = -0.072 to 0.133).DiscussionThese cross-sectional findings suggest differential associations between withdrawal subtypes and well-being in Chinese cultural contexts.